Profitability and Efficiency of Red Onion Farming - Rosyadi, Imron; Purnomo, Didit (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2014)
The purpose of this research is to determine and analyze the profitability and performance of onion farming marketing margins; analyze and know the parts of prices received by farmers and analyze the efficiency of onion farming in the district of Brebes. Samples taken in this study is 30 onion farmers in the district of Brebes, who settled in six villages, each village was taken 5 farmers as the research sample. These results indicate that the location of onion farming research does not provide benefits significantly to the household economy of farmers. Higher selling prices at the retail level and supermarkets do not have a significant impact on the level of profits of farming in the study area. Farming is done by farmers in the study area is inefficient. Onion marketing chain in the study area is relatively long, which consists of 4 lines of marketing.